2010
DOI: 10.2215/cjn.06770909
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Study Comparing Once-Weekly to Every-2-Week and Every-4-Week Dosing of Epoetin Alfa in CKD Patients with Anemia

Abstract: Background and objectives: Extended-interval dosing of epoetin alfa (EPO) is commonly used to treat anemia in patients with chronic kidney disease (CKD).This study aimed to demonstrate that EPO dosed every 2 weeks (Q2W) and every 4 weeks (Q4W) was noninferior to once-weekly (QW) dosing.Design, setting, participants, & measurements: 430 anemic subjects with stage 3 to 4 CKD receiving a stable QW dose of EPO were randomized 1:1:2 to QW, Q2W, and Q4W dosing for 36 weeks. Hemoglobin (Hb) was measured weekly, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In addition, 92 potentially relevant systematic reviews were identified and screened, 10 of which were evaluated in full-text; 172 potentially relevant citations were identified from the references of these systematic reviews, of which 23 satisfied the selection criteria. After removal of duplicate reports, 31 unique trials with 72 study arms (cohorts) were included 8,28–57 . All eligible studies were in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 92 potentially relevant systematic reviews were identified and screened, 10 of which were evaluated in full-text; 172 potentially relevant citations were identified from the references of these systematic reviews, of which 23 satisfied the selection criteria. After removal of duplicate reports, 31 unique trials with 72 study arms (cohorts) were included 8,28–57 . All eligible studies were in English.…”
Section: Resultsmentioning
confidence: 99%
“…The attrition rates over the full duration of follow-up, reported in 29 trials, ranged from 0% to 80%. Six trials reported drop-out rates of less than 10% 29,31,35,49,56,57 and 7 trials of more than 40% 33,37,38,41,43,46,48 . Two trials did not report their drop-out rates 39,53 .…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, several studies have demonstrated that equivalent target hemoglobin levels can be maintained at much lower doses of epoetin alfa when administered subcutaneously than intravenously [17,18]. Indeed some have shown that subcutaneous epoetin alfa dosing frequency can be reduced in some patients to once every 2–4 weeks, without compromising efficacy and potentially reducing subject burden and costs [19].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several studies have demonstrated that equivalent target hemoglobin levels can be maintained at much lower doses of epoetin alfa when administered subcutaneously than intravenously [17,18]. Indeed some have shown that subcutaneous epoetin alfa dosing frequency can be reduced in some patients to once every 2-4 weeks, without compromising efficacy and potentially reducing subject burden and costs [19]. We employed weekly administration of epoetin alfa, as it has been shown to be effective in maintaining hemoglobin concentrations in the majority of stable hemodialysis patients [20], among subjects with chronic kidney disease but not on dialysis [21] and in HIV positive subjects [22].…”
Section: Dosing Of Esamentioning
confidence: 99%
“…Subsequent research demonstrated that equal therapeutic effect (Hb control) could be achieved with much lower individual/total weekly doses (e.g., 3-fold lower), and with less frequent dosing, e.g., twice or once/week (not affecting drug utilization). It has been further demonstrated that subcutaneous (s.c.) administration (particularly convenient for patients not yet on dialysis) allows for further reduction in drug utilization (by 20-30%) with additional flexibility in dosing, showing equivalent therapeutic effect and drug utilization with thrice, twice or once a week dosing (tiw, biw, qw, respectively), or even with once every 2 weeks (q2w) or every 4 weeks (q4w) dosing [5][6][7]. This flexibility allows for individualization of treatment in agreement with the (desired) therapeutic effect, rationalization of drug utilization and also contributes to lower occurrence of adverse effects [5][6][7].…”
Section: Erythropoisis Stimulating Agents: Recombinant Human Erythropmentioning
confidence: 99%